1992
DOI: 10.1152/ajpheart.1992.262.4.h1054
|View full text |Cite
|
Sign up to set email alerts
|

Plasma volume expansion with colloids increases blood-tissue albumin transport

Abstract: Extravasation of plasma proteins is increased after volume expansion with whole blood or plasma. To investigate the mechanisms responsible for this phenomenon, we measured extravascular accumulation of exogenous 131I-labeled bovine serum albumin in several tissues and organs of anesthetized rats. Plasma volume was increased acutely by infusion of isoncotic albumin or polyvinylpyrrolidone, with or without subsequent infusion of a 1:10 dilution of the colloid to induce blood-to-tissue fluid movement. Controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…Renkin et al [1] reported the increased elimination of 125 I-labelled albumin 30 and 60 min after letting iso-oncotic albumin expand the plasma volume by 80-90 % in rats. Albumin uptake was found in the viscera, heart and skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renkin et al [1] reported the increased elimination of 125 I-labelled albumin 30 and 60 min after letting iso-oncotic albumin expand the plasma volume by 80-90 % in rats. Albumin uptake was found in the viscera, heart and skin.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma concentrations of infused proteins increase, whereas the dilution resulting from the plasma volume expansion reduces the concentrations of other proteins. Moreover, the transport of albumin from blood to the interstitial fluid increases [1]. The sum of these alterations may be relevant to postoperative morbidity and to critical illness, which includes organ dysfunction associated with a high transcapillary escape rate for proteins [2,3] and coagulation disorders [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the intact animals [7,9,10] circulation was driven by the heart, by a pulsatile (confirmed by Rippe) pump in the isolated limbs, vasodilatated by papaverine [8]. Vasodilatation may have occurred in the plasma volume-expanded rats, e.g., because increased central venous pressure did not raise arterial pressure [9]. Does very high P V enhance [8] or induce [10] vasodilatation metabolically?…”
mentioning
confidence: 97%
“…Might the explanation reside in two sets of pores ( Figure 1)? Small pores of the glycocalyx which lines the luminal side of endothelial cells, fenestrae and cell junctions permit filtration of very low-protein fluid, while very sparse large pores offer little resistance to convection of protein [6][7][8][9][10][11]. Increase of COP t seems to oppose absorption at small pore ( Figure 1B) and fenestral exits [11].…”
mentioning
confidence: 98%
See 1 more Smart Citation